2019
DOI: 10.1016/j.jcmg.2018.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Abnormal Septal Motion in Left Bundle Branch Block

Abstract: Objectives: This study sought to investigate how regional left ventricular (LV) function modifies septal motion in left bundle branch block (LBBB). Background: In LBBB the interventricular septum often has marked pre-ejection shortening, followed by immediate re-lengthening (rebound stretch). This motion, often referred to as septal flash, is associated with positive response to cardiac resynchronization therapy (CRT). Methods: In 10 anesthetized dogs we induced LBBB by radiofrequency ablation and occluded the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…less "wasted" work) implies also, that the potential to improve septal function is A c c e p t e d m a n u s c r i p t reduced. At the same time, the lateral wall is exposed to less pre-stretch and performs therefore less work, which explains that here the potential for unloading by CRT is lower 18,19 .…”
Section: Distribution Of Regional Myocardial Work Before Crtmentioning
confidence: 91%
See 1 more Smart Citation
“…less "wasted" work) implies also, that the potential to improve septal function is A c c e p t e d m a n u s c r i p t reduced. At the same time, the lateral wall is exposed to less pre-stretch and performs therefore less work, which explains that here the potential for unloading by CRT is lower 18,19 .…”
Section: Distribution Of Regional Myocardial Work Before Crtmentioning
confidence: 91%
“…Adding information on ischemic aetiology to myocardial work mattered only before CRT, which indicates that work heterogeneity found before CRT is not only the result of loading differences which can be treated by resynchronization, but has likely also an ischemic component. Indeed, total myocardial scar burden has been shown before to be associated with non-response to CRT 23 , and a LBBB-pattern of work distribution may be mimicked by a septal scar, which also reduces septal work 19 . In such hearts, successful redistribution of myocardial work may not be possible by means of CRT which, however, becomes only overt after CRT-implantation if scar is not recognized.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Our group has performed several studies on LBBB and CRT where sonomicrometric crystals have been implanted which allows analysis of SF ( Gjesdal et al, 2011 ; Aalen et al, 2019 ; Andersen et al, 2021 ). This study was therefore a combination of retrospective analysis of previously performed experiments ( n = 4) and a prospective study where EM tracking sensors were implanted ( n = 22).…”
Section: Methodsmentioning
confidence: 99%
“…The motion may be small or absent in the presence of septal scar, impaired global or right ventricular (RV) contractility or RV volume overload ( Remme et al, 2016 ). However, SF assessed by echocardiography or other imaging technologies has been shown to be a reliable predictor of CRT response ( De Boeck et al, 2009 ; Sohal et al, 2014 ; Risum et al, 2015 ; Aalen et al, 2019 ). The correction of this abnormal septal motion by CRT indicates an increased likelihood of LV volumetric reverse remodeling ( Jansen et al, 2007 ; Parsai et al, 2009 ; Stankovic et al, 2016 ) and some studies have shown ability to predict long term response ( Menet et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial work is an alternative tool for studying LV function through incorporating deformation and LV pressure into its analysis (5). A growing amount of evidence supports the use of myocardial work to detect early-stage heart diseases, aid prognostication, and predict therapeutic responses (6)(7)(8)(9)(10)(11)(12)(13)(14). However, myocardial work has not been studied in a ventricular pre-excitation setting.…”
Section: Introductionmentioning
confidence: 99%